A Pre-Experimental Study to Evaluate the Effect of ICU Prophylaxis Program in Improving the Knowledge, Practices Related to Pressure Ulcers and Deep Vein Thrombosis in Spinal Cord Injury Patients and its Acceptability by the Nurses in a Tertiary Care.... - Toseef M RN; Joshi P RN; Sinha S (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Good nursing care is a key factor in reducing the most common complications related to immobility like pressure ulcers (PU), deep vein thrombosis (DVT) in spinal cord injury (SCI) patients. Materials and methods: The study was conducted using a pre-experimental, time series design on 52 nurses and 73 patients with SCI (30 before and 43 after the intervention) enrolled by universal sampling technique in a trauma ICU of a tertiary care facility to evaluate the effectiveness of ICU Prophylaxis  Programme (IPP) in terms of knowledge, practices related to PU and DVT in SCI patients and its acceptability by the nurses. Pretested and validated tools were used to collect the data. Occurrence of the PU and DVT were assessed among the admitted SCI patients during the study period as secondary outcome. Results: There was signifi cant improvement in knowledge scores of nurses (in post-test 1) following the implementation of IPP in PU (12.87 ± 2.37 vs. 16.23 ± 1.60, p < 0.001) and DVT (12.90 ± 2.30 vs. 17.08 ± 1.49, p < 0.001), however slight reduction in knowledge scores was observed on 15th day (post -test 2) in PU (15.77 ± 1.88, p ≥ 0.269) and DVT (16.29 ± 1.80, p ≥ 0.219) as compared to post-test 1. There was also signifi cant improvement in practice scores of nurses following the implementation of IPP in PU (6.23 ± 1.57 vs. 8.44 ± 1.046, p < 0.001) and in DVT (1.55 ± 1.17 vs. 8.21 ± 1.28, p < 0.001) on 15th day. Majority of nurses (84.6%) expressed moderate acceptability towards the IPP. The occurrence of the PU reduced from 16.6% to 4.6% after IPP and the use of mechanical prophylaxis for the prevention of DVT increased. Conclusion: IPP improved the knowledge and practice scores of the nurses in PU and DVT and reduced the occurrence of PU among SCI patients and increased the use of mechanical prophylaxis for prevention of DVT among admitted SCI patients.